Study on the Influence and Deformation Control of Rich Water Foundation Excavation on Adjacent Buildings - Zhouya Wang; Xiaole Shen; Xiaoxu Tian; Zhanping Song; Pengyuan Zhou (Buildings)
Taking the foundation pit of the Suzhou Chunshenhu Road Expressway Reconstruction Project as an example, the excavation process of the foundation pit was numerically simulated using a three-dimensional finite element method. The measured data and simulated data of the lateral deformation of the enclosure structure, surface settlement deformation of the ground outside the pit, and settlement deformation of the building were compared to analyze the impact of foundation pit construction on adjacent buildings. The influence of foundation pit floor and diaphragm wall thickness on wall displacement, building settlement, and foundation pit uplift was also discussed. The results showed the following: (1) Adding a foundation pit floor has a significant effect on reducing the lateral displacement of the diaphragm wall, settlement of the building, and uplift of the foundation pit. Increasing the thickness of the foundation pit floor has a limited effect on reducing the displacement, while increasing the thickness of the diaphragm wall has a small effect. (2) The displacement curve of the underground diaphragm wall increases with depth. It reaches a maximum at the excavation surface and then decreases gradually. (3) The surface settlement increases first and then decreases with distance from the foundation pit, showing a concave shape. As the depth of excavation increases, the settlement value increases. (4) Through analysis of the monitoring data of vertical displacement of buildings, it can be seen that during foundation pit excavation, buildings undergo five stages: initial slow descent, steep descent, mid-term slow descent, late steep descent, and stable deformation. The buildings are dominated by settlement deformation.